Improved thermoelectric properties of nanostructured composites out of Bi1-xSbx nanoparticles and carbon phases - Günes, Ekrem; Wickleder, Mathias S.; Müller, Eckhard; Elm, Matthias T.; Klar, Peter J.; Justus Liebig University Giessen (My University, 2018)
Thermoelectric figures of merit of ZT ≈ 0.4 at room temperature were achieved in nanostructured composite materials prepared by uniaxial pressing of Bi1-xSbx nanoparticles and 0.3 wt.% of a carbon phase. This constitutes a significant improvement of the low-temperature thermoelectric material Bi1-xSbx and strongly suggests the possibility of employing these materials in efficient thermoelectric devices working at room temperature. Interestingly, the beneficial effect of the carbon phase added to nanostructured Bi1-xSbx is the same for either carbon nanotubes or active carbon. This finding is attributed, on the one hand, to a combination of electronic band gap engineering due to nanostructuring and energy filtering due to graphene-like interlayers between Bi1-xSbx grains and, on the other hand, to modified phonon scattering at the grain boundaries and additional phonon scattering by agglomeration sites of carbon material on the micro m scale.
Keywords: ddc:540